2015
DOI: 10.1002/adhm.201400817
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Complexed with Gene Vectors to Promote Proliferation of Human Vascular Endothelial Cells

Abstract: Amphiphilic block copolymers containing biodegradable hydrophobic segments of depsipeptide based copolymers have been synthesized and explored as gene carriers for enhancing proliferation of endothelial cells in vitro. These polymers form nanoparticles (NPs) with positive charges on their surface, which could condense recombinant plasmids of enhanced green fluorescent protein plasmid and ZNF580 gene (pEGFP-ZNF580) and protect them against DNase I. ZNF580 gene is efficiently transported into EA.hy926 cells to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 73 publications
1
51
0
Order By: Relevance
“…The main reason was the degradation product (L-alanine) of MMD in P(LA-co-GA-co-MMD) copolymers might promote the proliferation of HUVECs via a signal pathway [43]. These results were in good agreement with our previous studies [42,46]. MMD) nanofibrous scaffolds increased with the increasing contents of MMD in copolymers and HUVECs on the P(LA-co-GA-co-MMD)3 scaffolds exhibited the highest relative cell viability.…”
Section: Proliferation Of Huvecs On Plga and P(la-co-ga-co-mmd) Scaffsupporting
confidence: 91%
See 1 more Smart Citation
“…The main reason was the degradation product (L-alanine) of MMD in P(LA-co-GA-co-MMD) copolymers might promote the proliferation of HUVECs via a signal pathway [43]. These results were in good agreement with our previous studies [42,46]. MMD) nanofibrous scaffolds increased with the increasing contents of MMD in copolymers and HUVECs on the P(LA-co-GA-co-MMD)3 scaffolds exhibited the highest relative cell viability.…”
Section: Proliferation Of Huvecs On Plga and P(la-co-ga-co-mmd) Scaffsupporting
confidence: 91%
“…Moreover, the degradation products of MMD including L-amino acids can stimulate the proliferation of endothelial cells via a signal pathway and be properly metabolized by living tissues [42][43][44][45]. Based on the copolymers of MMD with other cyclic monomers, our group have developed some gene delivery systems for promoting the transfection and migration of endothelial cells [42,[46][47][48][49]. However, to the best of our knowledge, the study on electrospun nanofibrous scaffolds from the copolymers of MMD with other cyclic monomers for vascular tissue engineering has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…22 In our previous studies, several gene carriers to condense with pEGFP-ZNF580 gene (pEGFP-ZNF580 gene is the recombinant plasmid of enhanced GFP plasmid and ZNF580 gene) were prepared with different block copolymers for the proliferation of ECs. [23][24][25][26][27][28][29] As the "gold" standard nonviral gene carrier, polyethylenimine (PEI) is widely used as an effective gene carrier, which exhibits a good performance in condensing DNA due to its high positive charge density. 30 However, the drawbacks of high-molecular weight PEI, including nondegradability and high cytotoxicity, limit its application in vivo.…”
Section: Feng Et Almentioning
confidence: 99%
“…[13][14][15][16][17][18] For example, Lv et al reported that a complex micelle consisting of a biodegradable PLGA core and a mixed PEG/PEI shell can be prepared via the self-assembly of two block copolymers (PEG-b-PLGA and PLGA-b-PEI) in aqueous solution. This micelle can be used as a gene carrier for enhancing proliferation of endothelial cells.…”
mentioning
confidence: 99%
“…17 Recently, Li et al developed a new kind of gene carrier based on the amphiphilic block copolymers containing biodegradable hydrophobic depsipeptide copolymers and branched PEI. 18 We have also developed a novel type of PEI-based amphiphilic core-shell nanoparticles (NPs) with diameters in the range of 100-300 nm and explored their potential application as nanocarriers for drug and gene deliveries. [19][20][21] Compared with the abovementioned micellarbased biodegradable NPs, the PEI-based core-shell NPs possess several distinct advantages: 1) PEI@poly(methyl methacrylate) (PMMA) core-shell NPs with adjustable diameters ranging from 100 nm to 300 nm can be easily synthesized and scaled up; 2) the PEI shells allow rapid and efficient encapsulation of DNA molecules through the electrostatic complexation; 3) the immobilized PEI is three to four times less toxic than the native free PEI and is at least threefold more efficient as gene carriers in transfecting cells; 4) the amount of PEI needed to form complexed NPs with DNA molecules can be significantly reduced when using preformed uniform core-shell NPs containing PEI shells; and 5) the resulting DNA/NP complexes are highly uniform and homogeneous, providing good delivery system for pharmacokinetic studies.…”
mentioning
confidence: 99%